The role of thiol redox systems under a combined action of extreme temperatures and antibiotics in Escherichia coli - Smirnova, G.V.; Lepekhina, E.V.; Muzyka, N.G.; Samoilova, Z.Y.; Tyulenev, A.V.; Bezmaternykh, K.V.; Peters, M.A.; Ushakov, V.Y.; Brysova, M.N. (Perm Federal Research Centre Journal, 2017)
Stresses induced by abrupt temperature shifts, antibiotics of different classes and by a combined action of nonoptimal growth temperatures and antibiotics are studied in bacteria Escherichia coli deficient by components of redox systems dependent on glutathione ( gshA, gor, grxA, grxB ) and thioredoxin ( trxA , trxB ). It is shown that the mutations under consideration significantly change the number of S-S bindings in proteins, the levels of oxidants (H2O2), reductants (glutathione) and the antioxidant gene expression, as well as the susceptibility of bacteria to antibiotics and extreme temperatures. The direction of influence (an increase or decrease in susceptibility) depends on the type of mutation and differs for antibiotics of different classes. Significant inverse correlations were observed between lgCFU (colony-forming units) and specific growth rate prior to antibiotic addition under all the situations investigated: the effect of mutations on the antibiotic activity at an optimal growth temperature, the effect of combined stresses and the effect of supplements that change the redox state.